The effectiveness of using crossword puzzle games to improve vocabulary mastery of the 7th grade students of SMP Muhammadiyah 2 Kalasan - Bambang Pratolo; Riqqah Hafizhah (Universitas Ahmad Dahlan, 2022)
Vocabulary mastery plays an important role in learning English. The role of a teacher is important in helping students achieve their goals because acquiring sufficient number of vocabularies is a basic requirement for mastering English. This study aims to investigate the effectiveness of using crossword puzzles to improve vocabulary mastery. This research was conducted at SMP Muhammadiyah 2 Kalasan. This research was conducted using an experimental design, especially a quasi-experiment using a quantitative approach. The population used in this study was the seventh-grade students of SMP Muhammadiyah 2 Kalasan. The sample used in this study was class 7 students of SMP Muhammadiyah 2 Kalasan totaling 36 people consisting of 2 classes, namely class 7d as the control class and class 7e as the experimental class. The instruments used in this study were test questions in the form of multiple-choice as many as 20 test items. Data collection techniques in this study used pretest, treatment, and posttest.The results of this study stated that the use of crossword puzzles could effectively increase vocabulary mastery of the students. From the results of SPSS calculations, the scores obtained by the experimental class after the treatment was carried out were higher than before. So from the hypothesis test, it was found that the value of Sig was 0.00 which was < 0.05 and thus the H0 was not accepted, and Ha was accepted. It means that media Crossword Puzzle (X) affects mastery of English vocabulary (Y). Therefore, the use of crossword puzzle influenced the increment of English vocabulary mastery among the seventh-grade students of SMP Muhammadiyah 2 Kalasan.